Food Safety Some Global Trends - El-Samragy, Yehia (IntechOpen, 2018)
Food safety is defined as the concept that food will not cause harm to the consumer when it is prepared and/or eaten according to its intended use. Most food product recalls and food-related outbreaks are fully considered as food safety failures. Many risk-based food safety standards, e.g., HACCP, BRC, SQF, ISO/FSSC 22000, are designed to prevent such issues from occurring. Any food recall or food-related outbreak may be attributed to the likelihood of a risk assessment, which in some way failed to identify and control the risk. The essence and true nature of food safety hazards are affected by resources of the food facility, e.g., human, work environment, infrastructure, availability and accessibility of food safety information. Thus, food specialists should establish and manage the parameters of the applied food safety systems to achieve the food safety objectives that produce food in compliance with regulatory and statutory requirements. It is important to understand what exactly will make an end product unsafe and ensure that the necessary control measures are in place to prevent it from happening. Understanding the basic food safety concepts can lead to improvement of the current food safety systems and/or standards.